Identification of lncRNAs involved in response to ionizing radiation in fibroblasts of long-term survivors of childhood cancer and cancer-free controls - Grandt, Caine Lucas; Brackmann, Lara Kim; Poplawski, Alicia; Schwarz, Heike; Marini, Federico; Hankeln, Thomas; Galetzka, Danuta; Zahnreich, Sebastian; Mirsch, Johanna; Spix, Claudia; Blettner, Maria; Schmidberger, Heinz; et al. (Frontiers in Oncology, 2023)
Introduction: Long non-coding ribonucleic acids (lncRNAs) are involved in the cellular damage response following exposure to ionizing radiation as applied in radiotherapy. However, the role of lncRNAs in radiation response concerning intrinsic susceptibility to late effects of radiation exposure has not been examined, let alone in long-term survivors of childhood cancer with and without potentially radiotherapy-related second primary cancers. Methods: Primary skin fibroblasts (n=52 each) of long-term childhood cancer survivors with a first primary cancer only (N1), with at least one second primary neoplasm (N2+) as well as tumor-free controls (N0) from the KiKme case-control study were matched by sex, age, and additionally by year and entity of the first primary cancer. Fibroblasts were exposed to 0.05 and 2Gray (Gy) X-rays. Differentially expressed lncRNAs were identified with and without interaction terms for donor group and dose. Weighted co-expression networks of lncRNA and mRNA were constructed using WGCNA. Resulting gene sets (modules) were correlated to the radiation doses and analyzed for biological function. Results: After irradiation with 0.05Gy, few lncRNAs were differentially expressed (N0: AC004801.4; N1: PCCA-DT, AF129075.3, LINC00691, AL158206.1; N2+: LINC02315). In reaction to 2Gy, the number of differentially expressed lncRNAs was higher (N0: 152, N1: 169, N2+: 146). After 2Gy, AL109976.1 and AL158206.1 were prominently upregulated in all donor groups. The co-expression analysis identified two modules containing lncRNAs that were associated with 2Gy (module1: 102 mRNAs and 4 lncRNAs: AL158206.1, AL109976.1, AC092171.5, TYMSOS, associated with p53-mediated reaction to DNA damage; module2: 390 mRNAs, 7 lncRNAs: AC004943.2, AC012073.1, AC026401.3, AC092718.4, MIR31HG, STXBP5-AS1, TMPO-AS1, associated with cell cycle regulation). Discussion: For the first time, we identified the lncRNAs AL158206.1 and AL109976.1 as involved in the radiation response in primary fibroblasts by differential expression analyses. The co-expression analysis revealed a role of lncRNAs in the DNA damage response and cell cycle regulation post IR. These transcripts may be targets in cancer therapy against radiosensitivity, as well as provide grounds for the identification of at-risk patients for immediate adverse reactions of healthy tissues. With this work we deliver a broad basis and new leads for the examination of lncRNAs in the radiation response.